One year prospective survey of azole resistance in Aspergillus fumigatus at a French cystic fibrosis reference centre: prevalence and mechanisms of resistance. (30th April 2019) - Lavergne, R -A; Morio, F; Danner-Boucher, I; Horeau-Langlard, D; David, V; Hagen, F; Meis, J F; Le Pape, P
Abstract: Background: Studies on Aspergillus fumigatus azole resistance in cystic fibrosis patients are scarce despite the fact that it is the most frequently isolated fungus from respiratory samples from these individuals. Objectives: To evaluate resistance prevalence, investigate mechanisms of resistance and explore the relationship between resistant isolates by genotyping. Methods: We conducted a prospective 1 year study (from 1 January to 31 December 2015), based on the investigation of up to five colonies per sample from cystic fibrosis patients. Results: Twenty-three (6.5%) isolates among the 355 tested were resistant to at least one triazole drug, using the EUCAST reference method, leading to a prevalence of 6.8% (6/88 patients). Analysis of resistance mechanisms highlighted TR34 /L98H ( n =  10), TR46 /Y121F/T289A ( n =  1), WT cyp51A ( n =  11) and F46Y/M172V/N248T/D255E/E427K ( n =  1). No genotype was shared between patients. Conclusions: This study showed a relatively stable resistance prevalence in comparison with the previous study conducted in 2010–11 (8%), although resistance mechanisms varied between the two studies.